2020
DOI: 10.1186/s12957-020-01997-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of long-term outcomes in 44 patients following pelvic exenteration due to cervical cancer

Abstract: Background: Pelvic exenteration (PE) may be associated with prolonged overall survival (OS) in selected patients with advanced or recurrent cervical cancer. However, the factors related to improved survival following PE are not clearly defined. The aim of this study was to perform a retrospective analysis of OS rates in a group of patients undergoing PE in order to identify the factors related to improved long-term outcomes. Methods: Our study group consisted of 44 patients, including 21 squamous cell cancer (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…The most important parameter in the evaluation of risk related to the operative procedure is the mortality rate. Since the initial description, mortality rates have improved from higher than 30% to more acceptable rates of 0 to 10% with 5-year OS varying between 20 and 60%, despite the high morbidity rate (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(21)(22)(23)(24). In the present study, there was one perioperative death (4.3%) due to a sudden pulmonary embolism, despite prophylactic anticoagulant protocol during hospitalization and home discharge and patient early mobilization.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The most important parameter in the evaluation of risk related to the operative procedure is the mortality rate. Since the initial description, mortality rates have improved from higher than 30% to more acceptable rates of 0 to 10% with 5-year OS varying between 20 and 60%, despite the high morbidity rate (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(21)(22)(23)(24). In the present study, there was one perioperative death (4.3%) due to a sudden pulmonary embolism, despite prophylactic anticoagulant protocol during hospitalization and home discharge and patient early mobilization.…”
Section: Discussionmentioning
confidence: 52%
“…In our study, 11 out of the 23 patients (47.8%) with primary pelvic exenterations had fistulas at the moment of surgery, a condition that inevitably alters the quality of life of these patients and that will not be solved by oncologic treatment. The 5-year OS after pelvic exenterations which ranges between 20 and 60% in all studies, when the oncological indications and contraindications are respected (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(22)(23)(24)(25)(26), is similar or higher compared to the OS after chemoradiotherapy for these advanced pelvic cancers, considered separately. Kramer et al (25) reported that 22% of his patients who underwent radiochemotherapy for locally advanced cervical cancer with curative intent developed fistulas, and the 5-year survival rate was 18%.…”
Section: Discussionmentioning
confidence: 83%
“…In our study, 11 out of the 23 patients (47.8%) with primary pelvic exenteration had urinary or rectal stulas at the moment of surgery, a condition that will alter enormously their quality of life and that will not be solved by oncologic treatment. The 5-year overall survival after pelvic exenteration, which ranges between 20% and 60% in all studies, when the oncological indications and contraindications are respected [5][6][7][8][9][10][11][12][13][14][22][23][24][25][26], is similar or higher compared to overall survival after chemoradiotherapy for these advanced pelvic cancers, considered separately. Kramer [25] reported that 22% of his patients who underwent radiochemotherapy for locally advanced cervical cancer with curative intent have developed stulas, and the 5 years survival rate was 18%.…”
Section: Discussionmentioning
confidence: 91%
“…Squamous cell carcinoma is the most common pathological type of cervical cancer, followed by cervical adenocarcinoma and cervical adenosquamous carcinoma. Differences exist in the etiology, clinical features, response to radiotherapy and chemotherapy, and prognosis of patients with three pathological types of cervical cancer [16][17][18]. The National Comprehensive Cancer Network guidelines and FIGO guidelines do not distinguish the treatment of cervical adenocarcinoma and cervical adenosquamous carcinoma from that of cervical squamous cell carcinoma [3].…”
Section: Discussionmentioning
confidence: 99%